2018
DOI: 10.25034/ijcua.2018.3659
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetics of Space Organization: Lessons from Traditional European Cities

Abstract: A B S T R A C T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 7 publications
0
9
0
4
Order By: Relevance
“…In fact, the collective influence of aesthetics decisions on buildings are germane to the society and to the mental psychologically of individuals that make-up the society. In the overall, this study posits that the concept of Gestalt grouping, symbolic and formal aesthetic should be reinforced in design studio classes to strengthen the idea behind the aesthetics in cities through buildings (Nia and Suleiman, 2018).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In fact, the collective influence of aesthetics decisions on buildings are germane to the society and to the mental psychologically of individuals that make-up the society. In the overall, this study posits that the concept of Gestalt grouping, symbolic and formal aesthetic should be reinforced in design studio classes to strengthen the idea behind the aesthetics in cities through buildings (Nia and Suleiman, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…The term "Aesthetics" is used pertaining to beauty in architecture or art (Nia and Suleiman, 2018). Notwithstanding this, Gür…”
Section: Introductionmentioning
confidence: 99%
“…The study suggestions three priorities represented by character and identity, green design, incompatibility between identity and design [12]. Nia and Suleiman (2018) pointed the value of urban spaces and it's an important role in achieving the aesthetics of European cities. They showed that historical places acquire multiple values through it's growth stages.…”
Section: Background Of the Researchmentioning
confidence: 99%
“…Characteristic of the International style is the emphasis on austerity, clean lines, clinical white colors, bald facades and total rejection of ornaments. The hallmark of the style is its emphasis on volumes rather than mass, so much so that it portrays an aura of lightness and weightlessness using thin curtain walls, open plan spaces, machine aesthetics, up-to-minute innovations in building technology, prefabrications, and the honest use of materials (Nia, H., & Suleiman, 2018Colquhoun, 1962. The style supports that buildings should be designed to be rational and scientific in their organization which dictated the search for honesty, economy and utility that meets society's new needs while at the same time appealing to the aesthetic taste.…”
Section: Bauhaus Schoolmentioning
confidence: 99%